PERANAN MOTIVASI TERHADAP PERKEMBANGAN KETERAMPILAN FISIK MOTORIK PESERTA DIDIK DALAM PENDIDIKAN JASMANI - Siti Ayu Risma Putri (JURNAL PENDIDIKAN ROKANIA, 2017)
To be able to absorb the concepts of movement in physical education learning needs high motivation of each learner. A learner will have a good motivation ifdiligent and active in practice in this case the motivation is associated with seriousness and determination of students to do the exercises diligently and spirit, so that later these motivations will contribute to the individual to be able to learn quickly and carefully basic skills and motor skills. Rahyubi (2014209) there are several things that affect motor learning process, among other individual factors (intrinsic motivation), environment, equipment or facilities, and teachers (extrinsic motivation). Individual factors related to the potential, talent, ability, and willingness of a learner. From the above opinion can be oncluded that the two opinions are interrelated meanings, ie the same goal which is the perfection of physical and motor skills influenced by motivation. This makes the motivation is taken into account in the learning process of physical education, because motivation is part of the physical education learning related to physical and motor skills development.